Quality assessment of licorice (Glycyrrhiza glabra L.) from different sources by multiple fingerprint profiles combined with quantitative analysis, antioxidant activity and chemometric methods. (15th September 2020) - Yang, Fangliang; Chu, Tiantian; Zhang, Yujing; Liu, Xitong; Sun, Guoxiang; Chen, Zhenhong
Highlights: Wild and cultivated licorice samples from different habitats were collected. An evaluation method combining HPLC, UV and FT-IR fingerprints was proposed. Regional disparity of licorice was analyzed by quantitative determination with PCA. Correlation between antioxidant activity and licorice components was established. Abstract: Licorice, as a nutritional plant extensively used in food fields, grows in various origins of the world as wild and cultivated types. But existing methods were not adequate for quality estimation of licorice samples from multiple sources till date. In the present research, HPLC, UV and FT-IR were applied together to establish fingerprint profiles of licorice ( Glycyrrhiza glabra L.) samples. Then, an appropriate quantitative method was adopted to evaluate their qualities. Furthermore, eight active chemical compositions and the potential antioxidant capacities of licorice samples were determined, and their intrinsic characteristics were excavated by chemometric methods. The results showed that the ingredient content and antioxidant capacity of licorice were closely related to the origin and growth type, and the established method was capable of accurately classifying wild and cultivated licorice samples from nine habitats into five quality grades. This study provides a novel and comprehensive strategy for food quality assessment.